Using field sign surveys to estimate spatial distribution and territory dynamics following reintroduction of the Eurasian beaver to British river catchments. (9th December 2020) - Campbell‐Palmer, Róisín; Puttock, Alan; Wilson, Kelsey A.; Leow‐Dyke, Alicia; Graham, Hugh A.; Gaywood, Martin J.; Brazier, Richard E.
Abstract: Eurasian beavers, keystone species, have returned to inhabit much of its former range following near extinction. Evidence repeatedly demonstrates that beavers can provide important riparian biotic and abiotic ecosystem services. These abilities to modify their surroundings can cause conflict, especially in prime agricultural landscapes. Understanding how beavers are utilizing and expanding in European catchments is therefore essential. This paper presents a methodology by which the spatial extent and environmental impact of beavers can be quantified via distinctive field signs. This has widespread application in understanding their distribution, expansion, and any management implications. Its application is tested within two diverse case studies, the Tayside catchment, Scotland, and the Wye catchment, Wales/England, collectively covering >10, 000 km 2 of catchment area. A minimum of 114 active territories were identified in Tayside and a small number of free‐roaming beavers with no strong evidence of breeding territories were recorded on the River Wye. This study demonstrates that a detailed, time and cost efficient but also easily replicable, field survey method can allow estimates of beaver territorial zones when combined with geospatial analysis and expert assessment. As populations of Eurasian beavers continue to expand and be actively reintroduced across Europe, this survey‐based approach can be utilized to increase understanding of their distribution, population dynamics, and territorial behavior, as well as informing management strategies and identifying areas of potential benefit and/or conflict.